Al Kazemi Group - Esteban Rivera Becerra; Hussain Alajmi; Ahmed M A A Mubarak (International Journal of Tourism and Hospitality in Asia Pasific, 2019)
The study is about the Al kazemi Group in Kuwait. It is a large group and well knowned in service sector of the Kuwait. They are currently involved in the businesses related to shipping and logistics, travel and tourism, real estate, hospitality and FMCG (Fast moving consumer goods). N travel and tourism business they are working as the sales agents for many transportation companies like Royal Air Maroc, Aegean Airline and Egypt Air. In hospitality business they have established two hotels named as New Park Hotel and Latif Hotels. These hotels are considered among very top rated hotels in Kuwait. In the project the discussion is about the launch of bus service for the tourist in Kuwait. They could offer this service to the guests that stay in their hotels. They can make this service popular among the guests and the local citizens by providing it free of cost initially. The Al Kazemi group is already very famous in Kuwait and have very strong market position. They can bear the cost or expenditures incurred on the startup of this bus service. In this study, there is a complete discussion about the target market for this new idea in the business and there will be a complete analysis of economic, social, political and environmental effects of this new business idea. According to the analysis of external factors, it has been analyzed that these all are favorable in this business to accept the new idea as there is capacity for starting this unique service to enhance the productivity and the profitability of the recent business. According to the technological environment, it is analyzed in this study that these are also favorable as the transport industry of Kuwait is outstanding. There are some risks to start this new idea in the business which includes the threat for failure and the low acceptability from the customer side. With the failure of idea, there is a risk for losing the huge amount of capital which is a great loss to the company. This idea is sensible as it is the demand of the customers of this organization as it has been providing tourism services to the customers and with the introduction of transport facilities to its customers, there will be increasing attraction as the customers do not have need to go for finding another company to get the transport services for the tour in Kuwait and in its popular places. As the concluded remarks, it has been analyze that this business idea is sensible and most suitable for this organization as it has the positive results for organization.